Nociceptive and inflammatory mediator upregulation in a mouse model of chronic prostatitis. Issue 8 (August 2015) - Schwartz, Erica S.; Xie, Amy; La, Jun-Ho; Gebhart, G.F.
Abstract : Abstract: Chronic nonbacterial prostatitis, characterized by genitourinary pain in the pelvic region in the absence of an identifiable cause, is common in adult males. Surprisingly, the sensory innervation of the prostate and mediators that sensitize its innervation have received little attention. We thus characterized a mouse model of chronic prostatitis, focusing on the prostate innervation and how organ inflammation affects gene expression of putative nociceptive markers in prostate afferent somata in dorsal root ganglia (DRG) and mediators in the prostate. Retrograde tracing (fast blue) from the prostate revealed that thoracolumbar and lumbosacral DRG are the principal sources of somata of prostate afferents. Nociceptive markers (eg, transient receptor potential, TREK, and P2X channels) were upregulated in fast blue–labeled thoracolumbar and lumbosacral somata for up to four weeks after inflaming the prostate (intraprostate injection of zymosan). Prostatic inflammation was evident histologically, by monocyte infiltration and a significant increase in mast cell tryptase activity 14, 21, and 28 days after zymosan injection. Interleukin 10 and NGF were also significantly upregulated in the prostate throughout the 4 weeks of inflammation. Open-field pain-related behaviors (eg, rearing) were unchanged in prostate-inflamed mice, suggesting the absence of ongoing nociception, but withdrawal thresholds to lower abdominal pressure were significantly reduced. The increases in IL-10, mast cell tryptase, and NGF in the inflamed prostate were cotemporaneous with reduced thresholds to probing of the abdomen and upregulation of nociceptive markers in DRG somata innervating the prostate. The results provide insight and direction for the study of mechanisms underlying pain in chronic prostatitis. Abstract : This study provides an understanding of which nerves innervating the prostate contribute to maintenance of pain and hypersensitivity.